2013
DOI: 10.1371/journal.pone.0060445
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of KLHL3 in Complex with Cullin3

Abstract: KLHL3 is a BTB-BACK-Kelch family protein that serves as a substrate adapter in Cullin3 (Cul3) E3 ubiquitin ligase complexes. KLHL3 is highly expressed in distal nephron tubules where it is involved in the regulation of electrolyte homeostasis and blood pressure. Mutations in KLHL3 have been identified in patients with inherited hypertension disorders, and several of the disease-associated mutations are located in the presumed Cul3 binding region. Here, we report the crystal structure of a complex between the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 60 publications
15
100
0
Order By: Relevance
“…structures of BTB-Cul3 complexes have subsequently been solved (Errington et al 2012;Ji and Prive 2013), and these models confirmed that our mutagenesis approach targeted residues that contribute to the Cul3-BTB binding interface (Figure 4, A-B).…”
Section: Functional Dissection Of Kelch Molecular Activitiessupporting
confidence: 61%
See 3 more Smart Citations
“…structures of BTB-Cul3 complexes have subsequently been solved (Errington et al 2012;Ji and Prive 2013), and these models confirmed that our mutagenesis approach targeted residues that contribute to the Cul3-BTB binding interface (Figure 4, A-B).…”
Section: Functional Dissection Of Kelch Molecular Activitiessupporting
confidence: 61%
“…Kelch residues targeted in this study were generally not conserved in SPOP and were modeled into this representation using MacPyMol. The amino acid sequence positions targeted for mutagenesis are oriented toward Cul3, and each was found to contribute to the interaction surface in the solved structures (Errington et al 2012;Ji and Prive 2013). (C) Western analysis of ovaries from kel DE1 females rescued with Kelch containing the indicated mutations in the BTB domain.…”
Section: Functional Dissection Of Kelch Molecular Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many types of E3 ligases exist, but the Cullin-RING ligases (CRLs) constitute the largest family. CUL3 acts as the scaffolding protein of subfamily CLR3; in other words, it brings together the substrate recognition protein with the rest of the ubiquitination machinery (22,30). CUL3 binds to an adaptor protein of the BTB (Bric-a-brac, Tramtrack, and Broad complex)-containing family, which in turn binds to the substrate protein being ubiquitylated (8).…”
Section: Kelch3 and Cul3 Regulate Wnk Ubiquitination And Degradationmentioning
confidence: 99%